Avaliação das fibras colágenas em tumores mistos mamários de cadelas pela microscopia por geração de segundo harmônico (SHG) - Daiana Yively Osorio Taborda (2022)
The study of mammary tumors is essential in veterinary medicine because they are the most common neoplasms in female dogs. Within the tumors in the mammary gland, mixed tumors represent approximately 50% of the cases in the diagnostic routine, and the benign mixed tumor (BMT) and mixed tumor carcinoma (CMT) make up this group of neoplasms. Animals diagnosed with MSC have a good prognosis and a longer survival time compared to other mammary carcinomas. Although MSCs have good behavior and rarely develop metastasis, some cases progress to lymph node metastasis, thus changing the behavior and, consequently, the prognosis. Therefore, identifying changes in the tumor microenvironment (TME) may be responsible for the greater aggressiveness of CMT cancer cells. The microenvironment is integrated by all the elements that interact with cancer cells, including the extracellular matrix (ECM) and this is mainly composed of collagen fibers. In tumor progression, collagen fibers are the main target of cancer cells and their alterations facilitate the emergence of metastases. Thus, this study aimed to correlate changes in CMT collagen fibers that may be associated with the presence of lymph node metastasis. 46 cases of mixed tumors of the canine mammary gland were evaluated; 15 cases of benign mixed tumors, 16 cases of carcinoma in a mixed tumor without lymph node metastasis, and 15 cases of carcinoma in a mixed tumor with lymph node metastasis. The evaluation was performed using two-photon excitation microscopy, in which images were obtained in the areas of interest and data on collagen and cellular component were extracted. The analysis of the images and the comparison between the different tumor groups and control slides of normal canine mammary tissue stained in H&E allowed the evaluation of collagen fibers in the different stages of tumor progression. We demonstrated that collagen parameters correlate with clinical and pathological data such as the expression of immunohistochemical marker cyclooxygenase-2 (COX2). The results showed that the carcinomatous cases that evolved with lymph node metastasis have a shorter length of collagen fibers. It was also possible to observe that before the appearance of lymph node metastasis the fibers begin to align, thus facilitating the exit of cancer cells and consequently the progression of the disease. Finally, we observed that the number of collagen fibers correlated with COX2